Financial Performance Analysis Using the Value For Money Method at BPKAD Tidore Islands City, Indonesia for 2019-2023 Period - Huzaema, Nur Vanda; Dahlan, Fadli; Akbar, Asgar Ari (Manunggal Halim Jaya, 2025)
This study aims to determine the level of economy, efficiency, and effectiveness of financial performance at the Regional Financial and Asset Management Agency (BPKAD) of Tidore Islands City, 2019-2023, with a measurement method using the Value for Money method. The type of research used in this research is qualitative research. The results of this study indicate that 1). In terms of economic ratios, the financial performance of BPKAD of Tidore Islands city from 2019 to 2023 meets the Economic indicators 2. In terms of efficient ratios, the performance of BPKAD of the city of Tidore Islands from 2019 to 2023 meets the inefficient indicators. 3). Financial performance at BPKAD of Tidore Islands city in 2019 meets the Effective criteria, and in 2020, 2021, and 2022 meets the criteria for very Effective, while for 2023 it meets the criteria for ineffective. This finding shows significant fluctuations in financial performance, especially a decrease in effectiveness in the last year, which is a serious concern for the Agency. These results are important for evaluating ratio-based financial performance and making practical contributions in strengthening budget planning and control at the agency level.